Cannabidiol as a phytopharmaceutical for chronic pain: Integrative review (Research, Society and Development, 2024)
The aim was to analyze the use of cannabidiol as a medicinal treatment for chronic pain by means of an integrative review. This is an Integrative Literature Review (ILR), which set out to identify, synthesize and carry out an extended analysis of the herbal use of cannabidiol. Thirty pieces of literature were selected for full reading and presentation of the results, as they met the objectives. The samples came from 85% of the Medline/PubMed database, in the last five years, with 60% of them using a cross-sectional approach and descriptive nature, and 84% of the patients studied in the studies reported an improvement in the level of chronic and/or neuropathic pain after starting to use Cannabis. In addition to this benefit, others mentioned in the articles were improved sleep and its quality, as well as reduced opioid consumption. With regard to the origin of the pain, half said it was linked to one or more causes, and chronic pain including cancer (nonspecific, intractable and other) was the most mentioned (80%). There is important consensus that medical cannabis can be approved for populations with inflammatory, nociplastic, neuropathic and mixed pain, however, if you are considering using CBD to treat chronic pain or any other MMJ-based condition, it is essential to discuss this with a doctor or healthcare professional to ensure that it is safe and appropriate for your specific situation. In this sense, more studies should be carried out to prove the importance and effectiveness of cannabidiol in the treatment of chronic pain, both from a clinical, review and statistical point of view.